Special educational needs of students with autism spectrum disorders - Khaustov A.V (Moscow State University of Psychology and Education, 2016)
Education of children with autism spectrum disorders is possible only if their special educational needs are taken into account. Special educational needs of children form the demand for special educational conditions. On the basis of the existing primary list of special educational needs in the approximate adapted basic general education program for students with autism spectrum disorders and with consideration of contemporary scientific data about particularities of their development the structured list of 4 groups of basic educational needs was made. The first group of educational needs is the special organization of the educational process, the second - with the adaptation of the content of the educational program, the third - with adaptation of presentation of learning material, the fourth - with overcoming hardships in development, social skills and adaptation.